The acceptance of mobile learning for the subject of geography among pre university students (Form 6) / Dympna James Jemson, Sabariah Sharif and Soon Singh Bikar Singh - James Jemson, Dympna; Sharif, Sabariah; Bakar Singh, Soon Sigh (UiTM Press, 2020)
21st century technology and skills in education are two of the key issues in research over the years. Mobile learning has shown great potential of 21st century technology in education today. Technological developments such as mobile learning have changed the way students communicate, learn, think, and share information among them. This study was conducted to look at the acceptance of mobile learning among form 6 students in geography subjects. The quantitative method was used in this study involving 137 form 6 student from Pre University center located in the district of Kota Kinabalu, Sabah. All students taking geography subjects were taken as samples. The results from statistical analysis show that the acceptance level of students on mobile learning is in the high level.